Selective Targeting of the Repressive Transcription Factors YY1 and cMyc to Disrupt Quiescent Human Immunodeficiency Viruses - Barton, Kirston (Mary Ann Liebert, Inc., 2013)
Quiescent HIV-1 infection of resting CD4(+) T cells is an obstacle to eradication of HIV-1 infection. These reservoirs are maintained, in part, by repressive complexes that bind to the HIV-1 long terminal repeat (LTR) and recruit histone deacetylases (HDACs). cMyc and YY1 are two transcription factors that are recruited as part of well-described, distinct complexes to the HIV-1 LTR and in turn recruit HDACs. In prior studies, depletion of single factors that recruit HDAC1 in various cell lines was sufficient to upregulate LTR activity. We used short hairpin RNAs (shRNAs) to test the effect of targeted disruption of a single transcription factor on quiescent proviruses in T cell lines. In this study, we found that depletion of YY1 significantly increases mRNA and protein expression from the HIV-1 promoter in some contexts, but does not affect HDAC1, HDAC2, HDAC3, or acetylated histone 3 occupancy of the HIV-1 LTR. Conversely, depletion of cMyc or cMyc and YY1 does not significantly alter the level of transcription from the LTR or affect recruitment of HDACs to the HIV-1 LTR. Furthermore, global inhibition of HDACs with the HDAC inhibitor suberoylanilide hydroxamic acid (SAHA) enhanced the increase in LTR transcription in cells that were depleted of YY1.These findings show that despite prior isolated findings, redundancy in repressors of HIV-1 LTR expression will require selective targeting of multiple restrictive mechanisms to comprehensively induce the escape of quiescent proviruses from latency.